Issues with effective design of an ESL teacher professional development programme in Sabah, Malaysia - Wendy Hiew; Jill Murray (Penerbit UMS, 2018)
This study investigates English as Second Language teachers’ perceptions and the impact of the Professional Up-skilling of English Language Teachers programme, which was designed and conducted by the British Council Malaysia. A review of previous studies revealed a paucity of research focusing on large-scale, standardised teacher professional development programmes that involved English language teachers from both heterogeneous teaching levels (i.e. primary and secondary schools) and heterogeneous districts (i.e. urban and rural). The limited published studies available have been critical of this mode of professional development for a number of reasons, and the purpose of this study was to investigate these issues in the Malaysian context. A mixed methods explanatory sequential design was adopted, which utilised a questionnaire survey, interviews and focus group with the teachers and District English Language Officers. However, this article will focus on the qualitative findings. The findings reveal four major limitations of the programme: in the coursebook materials; negative emotional impact on the teachers, which compromised the potential benefits of the programme; selection of participants; and the amount of follow-up support. The findings have implication on programme designers and providers in designing future teacher professional development programmes.